Crassocephalum teysmannianum is a validly published and earlier name for Gynura daviesiae (Asteraceae: Senecioneae) - Zhu, Li-Cui; Hariri, Muhammad Rifqi; Li, Cheng-Sheng; Ren, Chen (Phytotaxa, 2025)
N/A